The Use of a Stand-Alone Interbody Fusion Cage in Subaxial Cervical Spine Trauma: A Preliminary Report - Brembilla, Carlo; Lanterna, Luigi Andrea; Gritti, Paolo; Signorelli, Antonio; Biroli, Francesco (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Anterior spinal surgery has a predominant role in the treatment of traumatic lesions of the subaxial cervical spine. Plating is considered indispensable to achieve stability but may cause dysphagia, dysphonia, and adjacent-level ossification. Zero-P (Synthes GmbH, Oberdorf, Switzerland), an anchored interdisc spacer, can be used without an associated plate. The present study aimed to test if this new implant would be associated with a low rate of dysphagia and other short-term complications compared with the standard for anterior spinal fusion surgery and would be able to achieve a solid fusion and maintain correct metamere alignment.Material and Methods This is a preliminary presentation of a clinical case series of patients with subaxial cervical injuries who underwent anterior interbody fusion. From July 2009 until September 2011, 12 patients were treated with a Zero-P cage. The data for analysis included operating time compared with the standard for spinal fusion surgery with a cage plus plate construct, intraoperative blood loss, clinical and radiographic results, and complications.Results In the postoperative period no patient had neurologic worsening. One patient experienced transient dysphonia and moderate dysphagia. All the patients were followed up for a minimum of 6 months (mean: 13 months; range: 6–27 months). Stability and fusion were obtained in all patients together with correct metamere alignment.Conclusion We presented the preliminary results of a clinical case series. Our results support the initiation of prospective randomized trials with more patients and longer follow-up.
Keywords: cervical spine; cervical injuries; anterior cervical fusion; stand alone; biomechanical evaluation